Smartphone-assisted personalized diagnostic devices and wearable sensors. (March 2020) - Purohit, Buddhadev; Kumar, Ashutosh; Mahato, Kuldeep; Chandra, Pranjal
Abstract: Personalized point-of-care (POC) devices offer an easy access for health monitoring without using sophisticated instruments. Recently, miniaturized biosensors are being widely used as POC devices because of their reliable, sensitive, and fast detection of biomolecules with portable features. The recent advances in the camera and processor of smartphones are being eagerly integrated with biosensing applications, and this can be a big boost for health-care diagnoses owing to their wider presence all over the world. In this review, we have discussed most recent developments of portable diagnostic devices and wearable sensors based on the combined features of smartphones and biosensors for POC applications. Optical, electrochemical, and wearable biosensors are discussed in detail, and their sensing mechanism using smartphones has been illustrated. To put perceptive insights into the importance of smartphone-based POC devices and wearable sensing devices, recent examples have been described including the sensor design, transduction mechanism, and smartphone integration.